PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, STRUKTUR AKTIVA DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Sri Wiranti Setiyanti; Dwi Prawani SR (JURNAL STIE SEMARANG, 2019)
Capital structure is the mix (proportion) of a company's long-term permanent funding indicated by debt, preferred stock equity and ordinary shares. The purpose of this study was to determine the effect of profitability, company size, asset structure and sales growth on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange in 2012 - 2016. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange ( IDX) in 2012-2016 totaling 149 companies. The sampling technique used a purposive sampling method so that the number of samples of 25 companies was obtained. The method of collecting data in this study is the documentation method. The data analysis method used is multiple linear regression. The results showed that the variable profitability and firm size did not have a significant effect on capital structure. Variable asset structure and sales growth had a significant effect on capital structure. Suggestions that can be given is that for future research, it is expected to increase the variables that affect capital structure such as liquidity ratios, business risks, liabilities and so on. For investors, it is necessary to look at the company's capital structure as a consideration for investing in order to get the return value as desired and for the manufacturing industry to be able to consider asset structure factors and maintain sales growth to remain stable in managing the company.